ANALISIS INTANGIBLE FACTORS YANG MEMPENGARUHI PENENTUAN HARGA PRODUK KARYA SENI - Kusriniarti Dwi Lestariningsih (Jurnal Teknosains, 2012)
This research aims to develop a new quantitative method to determine painting pricing based on 10 intangible factors, i.e. curator, amount of exhibition, painter’s year of birth, painting’s years of made, auction record,estimation price, exhibition place, painting media, painting size, and previous sales record. The selling price data are obtained from six auction houses. Kano Model and Linear Regression Model are used to examine the relationbetween pricing and each variable. Based on the model development scheme, there are 6 alternative models that can be obtained. Each model then was evaluated by cross-validation procedure using 21 data. Based on the value of R2for each model, the Kano Model with variable previous sales is the best model with R2 of 70%